Around Viewpoints from SITI-Company: Interview with Barney O'Hanlon by Tiago Porteiro (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
In this interview, carried out at the SITI-Company workspace (NY) , in May 2017, at the end of the III SITI-Company Conservatory, in which the interviewer participated, Barney O'Hanlon, member from SITI-Company since 1994, shares a critical biography about his own path, reflects on his personal practice through the Suzuki and Viewpoints training and composition systems, while analyzing structural dimensions and operating modes of this company of which he is a part. In this context, it stands out the fact that the interviewee presents himself, in the Viewpoints domain, as the member of SITI-Company that most articulates Anne Bogart's approach with that of Mary Overlie, the artist who was in the origin of Viewpoints and with whom he worked and developed a close relationship.
Keywords: SITI-Company; SITI-Conservatory; Viewpoints; Suzuki; Performing arts